2020
DOI: 10.1186/s13073-020-00751-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple approaches for massively parallel sequencing of SARS-CoV-2 genomes directly from clinical samples

Abstract: Background: COVID-19 (coronavirus disease 2019) has caused a major epidemic worldwide; however, much is yet to be known about the epidemiology and evolution of the virus partly due to the scarcity of full-length SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) genomes reported. One reason is that the challenges underneath sequencing SARS-CoV-2 directly from clinical samples have not been completely tackled, i.e., sequencing samples with low viral load often results in insufficient viral reads for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 46 publications
(51 reference statements)
4
129
0
3
Order By: Relevance
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24). However, several experimental issues, such as erroneous barcode sequencing, the production of primer dimers, and potential cross-contamination between runs, may complicate sequence-based analyses and impact the validity of NGS results (25,26).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24). However, several experimental issues, such as erroneous barcode sequencing, the production of primer dimers, and potential cross-contamination between runs, may complicate sequence-based analyses and impact the validity of NGS results (25,26).…”
Section: Discussionsupporting
confidence: 54%
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 48%
“…The availability of high-throughput sequencing approaches has enabled researchers to sequence genomes as the pandemic progressed in their respective countries. A number of methods have been adopted for rapid high throughput sequencing of SARS-CoV-2 including shotgun sequencing [4] , PCR amplicon, and hybridization/capture-based enrichment and sequencing [5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
“…A number of approaches have emerged for rapid and scalable sequencing of SARS-CoV-2 from clinical isolates. This includes direct shotgun approaches as well as targeted amplicon-based and targeted capture-based approaches [4][5][6] . Sequencing based approaches provide a unique opportunity for high fidelity of detection and for understanding the genetic epidemiology of SARS-CoV-2 [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Viral isolation and sequencing efforts throughout the world have permitted the interrogation of the SARS-CoV-2 genome, providing a deeper understanding of the evolution of the virus, its proximal origin and revealing patterns of its global spread [16, 17]. These efforts are largely centered on reverse transcription of the viral RNA genome followed by PCR amplicon and hybrid capture based sequencing using Oxford Nanopore and Illumina sequencers [18]. The sequences generated are largely deposited in data repositories such as the sequence read archive (SRA) and GISAID [19].…”
Section: Introductionmentioning
confidence: 99%